Publisher Correction: EMT cells increase breast cancer metastasis via paracrine GLI activation in neighbouring tumour cells. Issue 1 (December 2018) - Neelakantan, Deepika; Zhou, Hengbo; Oliphant, Michael; Zhang, Xiaomei; Simon, Lukas; Henke, David; Shaw, Chad; Wu, Meng-Fen; Hilsenbeck, Susan; White, Lisa; Lewis, Michael; Ford, Heide
This Article contains an error in Figure 2. In panel a, the second lane of the western blot should have been labelled 'siNT'. A correct version of Figure 2a appears in the Author Correction associated with this Article; the error has not been fixed in the original Article.